The Physiological Responses of Wheat and Maize Seedlings Grown under Water Deficit Are Modulated by Pre-Application of Auxin-Type Plant Growth Regulators - Dessislava Todorova; Zornitsa Katerova; Elena Shopova; Liliana Brankova; Iskren Sergiev; Jurga Jankauskienė; Sigita Jurkonienė (Plants, 2022)
The physiological responses of wheat and maize seedlings to exogenous auxin-type compounds 1-[2-chloroethoxycarbonyl-methyl]-4-naphthalenesulfonic acid calcium salt (TA-12) and 1-[2-dimethylaminoethoxicarbonylmethyl]naphthalene chlormethylate (TA-14) application prior to polyethyleneglycol-6000 (PEG) treatment were studied. PEG treatment inhibited seedlings growth and caused alterations in their antioxidant defence which was crop-specific. PEG increased the non-enzymatic antioxidants along with inhibition of enzymatic antioxidant activity in wheat, while in maize the opposite effects were found. The TA-12 and TA-14 applied alone increased most of the growth parameters measured in both crops, as well as the catalase activity and protein content of wheat. The growth of PEG-treated wheat and maize plants was improved by foliar spray with TA-compounds (TAs). Application of TAs before PEG treatment maintained low-molecular weight thiol-containing compounds and protein contents, and catalase and peroxidase activities close to the control levels. This was better expressed in maize than in wheat seedlings. The results showed that the preliminary application of TA-12 and TA-14 can reduce the adverse effects of moderate water deficit by crop-specific adjustment of the antioxidant defence to counteract stress.